S8‐Mediated Cyclization of 2‐Aminophenols/thiophenols with Arylmethyl Chloride: Approach to Benzoxazoles and Benzothiazoles. Issue 12 (24th May 2016) - Gan, Haifeng; Miao, Dazhuang; Pan, Qiang; Hu, Renhe; Li, Xiaotong; Han, Shiqing
Abstract: A metal‐free approach to benzazoles from arylmethyl chlorides and 2‐mercaptan/2‐hydroxyanilines using elemental sulfur as a traceless oxidizing agent has been developed. The reactions proceeded in good to excellent yields, exhibiting good functional groups tolerance and gram‐scale ability. A key mechanistic investigation indicated that the key intermediate trisulfide6, which was characterized by NMR, HRMS and crystal X‐ray crystallography, was separated in the reaction prior to the formation of the product. Abstract : A metal‐free approach to benzazoles from arylmethyl chlorides and mercaptan/2‐hydroxyanilines using elemental sulfur as a traceless oxidizing agent has been developed (see scheme). The reactions proceeded in good to excellent yields, exhibiting good functional groups tolerance and gram‐scale ability.